2011
DOI: 10.1111/j.1365-313x.2011.04560.x
|View full text |Cite
|
Sign up to set email alerts
|

Conserved differential expression of paralogous DEFICIENS‐ and GLOBOSA‐like MADS‐box genes in the flowers of Orchidaceae: refining the ‘orchid code’

Abstract: SUMMARYIn flowering plants, class-B floral homeotic genes encode MADS-domain transcription factors, which are key in the specification of petal and stamen identity, and have two ancient clades: DEF-like and GLO-like genes. Many species have one gene of each clade, but orchids have typically four DEF-like genes, representing ancient gene clades 1, 2, 3 and 4. We tested the 'orchid code', a combinatorial genetic model suggesting that differences between the organs of the orchid perianth (outer tepals, inner late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(114 citation statements)
references
References 56 publications
6
105
0
Order By: Relevance
“…Functional studies of the CYC-like genes in the grasses implicate them in the control of shoot branching (Doebley et al, 1995;Kebrom et al, 2006), inflorescence branch angle and leaf morphology (Bai et al, 2012), and lemma versus palea identity in rice (Yuan et al, 2009), not structural floral zygomorphy. In a number of orchids, the development of distinct second and third whorl tepals associated with zygomorphy is associated with variability in AP3/DEF homolog expression and variability in floral MADS box complex formation (Mondragón-Palomino and Theissen, 2008Theissen, , 2011Hsu et al, 2015). Aside from these sparse examples, the genetic underpinnings of floral zygomorphy in the broader monocots remain largely mysterious.…”
Section: Maize Floral Zygomorphy and B Class Functionmentioning
confidence: 99%
“…Functional studies of the CYC-like genes in the grasses implicate them in the control of shoot branching (Doebley et al, 1995;Kebrom et al, 2006), inflorescence branch angle and leaf morphology (Bai et al, 2012), and lemma versus palea identity in rice (Yuan et al, 2009), not structural floral zygomorphy. In a number of orchids, the development of distinct second and third whorl tepals associated with zygomorphy is associated with variability in AP3/DEF homolog expression and variability in floral MADS box complex formation (Mondragón-Palomino and Theissen, 2008Theissen, , 2011Hsu et al, 2015). Aside from these sparse examples, the genetic underpinnings of floral zygomorphy in the broader monocots remain largely mysterious.…”
Section: Maize Floral Zygomorphy and B Class Functionmentioning
confidence: 99%
“…B-class gene duplications followed by functional divergence have also been implicated in the formation of different tepal types in orchids (e.g. Chang et al, 2010;Mondragón-Palomino and Theissen, 2011). However, the evolution of petal-like sepals may not always involve shifts in B-class gene expression (Landis et al, 2012).…”
Section: Reviewmentioning
confidence: 99%
“…Phylogenetic analyses showed that orchid GLO-like genes form a single clade, which is duplicated once in the subfamily Orchidaceae , and these genes are expressed in all floral organs Mondragón-Palomino and Theißen, 2011;Pan et al, 2011;Tsai et al, 2005). By contrast, orchid has four well-supported lineages of DEF-like genes, which belong to Clade 1 to Clade 4 ( …”
Section: -3) Orchid Flowersmentioning
confidence: 99%